Perceived social support on quality of life in patients awaiting for coronary artery bypass grafting (CABG) surgery - Jamaludin, Sumaiyah @ ThandarSoe; Chong, Mei Chan (IIUM Press, International Islamic University Malaysia, 2017)
Coronary Artery Disease (CAD) is a major health problem due to its high prevalence, the steady increase in this occurrences and very high morbidity and mortality rates around the world. Furthermore, it is the most common leading causes of death in the world and the most common treatment for that is Coronary Artery Bypass Grafting (CABG) surgery. Patients who has been suffered from this disease and listed for CABG surgery should adapt themselves to overcome the changes in their new daily life. To overcome this, they should have effective social support to enhance their quality of life while awaiting for CABG surgery. Therefore, this study was aimed to explore the impact of perceived social support on quality of life in patients awaiting for Coronary Artery Bypass Grafting (CABG) Surgery.